(untitled) (Research, Society and Development, 2020)
The present study aimed to verify the presence of the main dyes used in food products intended for children by means of labeling. This is an exploratory, descriptive and quantitative study carried out in commercial establishments in the city of Teresina-PI. The verification of the dyes was through a photographic record of the labeling, in which the analyzed products were categorized based on the group of foods to which each product belongs and related them with the possible health effects. According to the results, natural dyes (41%) were the most present in foods, followed by artificial dyes (35%), with tartrazine (16.5%) being the most present, followed by twilight yellow and titanium dioxide, both with 14.3%. In the food groups, the presence of carmine in biscuits and stuffed cakes, annatto in snacks and in instant noodles and titanium dioxide in packaged juices stands out. Therefore, a considerable percentage of natural and artificial dyes was observed in the analyzed children’s products demonstrated their wide use in these products. However, there is no consensus on the health repercussions of consuming these dyes, requiring further experimental and longitudinal studies are needed to prove its long-term effect.